Current and Desired Organizational Culture at Universidad de Cuenca (2019-2021): Analysis from Cameron and Quinn’s Values Competition Model - Escudero Durán , Lorena (2022)
The purpose of this article is to expose current typologies, and desired organizational culture at Universidad de Cuenca. Analysis was developed according to values competition model by Cameron and Quinn. Mixed methodology was used, with an exploratory, and descriptive scope. Principal instrument used was OCAI test, and the application of interviews and focus groups to professors, students, and administrative staff, selected with a stratified probability sampling. Results indicate that the current type of organizational culture at Universidad de Cuenca is market type, with external orientation, and a structure that emphasizes stability, control, and strategic objectives fulfillment. In contrast, the desired culture is clan type, in which a familiar organizational environment is pursued, as well as the openness to share opinions, respect for diversity, and freethought.